PERBANDINGAN HUKUM TERHADAP STATUS BARANG AKIBAT PEMBATALAN KHITBAH SECARA SEPIHAK MENURUT EMPAT MADZHAB - Sukur, Mukhamad (IAIN Tulungagung, 2018)
ABSTRACTKhitbah is an attempt made by a man to engage a woman before they are married. This is done so that the man gets a partner in accordance to his expectation. With the sermon, the men and women will know each other more deeply. To reinforce a shared commitment to marriage bonds, sometimes the men give something, either in the form of goods or even dowries to the women. However, the proposal is not a binding contract to be carried out to the next stage, namely marriage. Because, the agreement in a contract has no power that is obligatory. Therefore, it may possible that each party brake the “khitbah”. The abrogation of such a sermon is very often in the community. The men or the women who are in the engagement may suddenly cancel the proposal although initially they have mutually committed to marry. Nevertheless, the termination of the proposal must be done in a good way and does not hurt any party. Although in Islamic teachings there is no material sanction in regard to the cancellation of the sermon it may have legal consequences for both parties in relation to the goods or dowries the men have given to the women. The study concludes that all scholars of the school of thought have the same opinion as to whether it is permissible for the men to reclaim the goods that have been given to the women. However, there is a difference of views in term of returning the goods in case there is physical damage. Among the four schools of thoughts, only the school of Hambali who holds that if his goods are lost or damaged, then it is not permissible to ask for the price or the gifts in return.Keywords: Khitbah, Perbandingan Hukum, Pembatalan Khitbah